INDICATEURS DE LA VARIABILITÉ CLIMATIQUE SUR LE COTONNIER DANS LA COMMUNE DE BANIKOARA AU NORD-EST BENIN - HOUNSOU, BIDOSSESSI MATHIEU; AHAMIDE, BERNARD (My University, 2022)
Water deficit remains one of the main limiting factors for agricultural production in Benin. This research aims to contribute to a better understanding of the indicators of climatic variability on cotton in the commune of Banikoara. This objective is achieved through a methodological approach that takes into account documentation, field work and data processing. Climatological data related to rainfall and temperature for the period 1960-2020 and producers' perceptions were used. Field surveys of producers and resource persons, i.e. one hundred and ninety-six (196) people, were carried out in ten (10) villages chosen according to their weight in cotton production. The results showed that seasonal rainfall totals, the number of rainy days and average monthly rainfall show a significant downward trend over the period 1960-2020. Temperatures have increased over the periods 1978-1989 and 1996-2020. The average temperature has increased by 1.9°C. The end and length of the rainy season have shown a significant trend towards earlier and shorter rainfall respectively. All these parameters have an impact on cotton production and yield.
Keywords: Indicateur; Cotonnier; Rendement; Variabilité Climatiques; Banikoara.